Islamic venture capital in Malaysia: development, constraints and way forward - Mikail , Sa'id Adekunle; Arifin, Mahama; Hassan, Rusni (Hamdan bin Mohammad e-University, 2014)
Purpose: This study aims at examining the development of the Malaysian Islamic venture capital industry including government and regulatory policy initiatives for escalating the growth of the industry. It also highlights constraints and way forward for the industry. Methodology: The paper employs qualitative approach focusing on secondary resources, documents, and field interview with practitioners and academia who are directly involved in the operations of Islamic venture capital in Malaysia. Findings: The study finds that policy-driven approach and liberalization facilitate the standardization of Shariah rulings of Shariah Advisory Council (SAC) and Shariah Committee (SC), which contribute to the effectiveness of regulatory framework and sustainable growth of the Islamic capital market in Malaysia. It also finds a number of constraints that dampen the progress of Islamic venture capital in Malaysia to be the following: i) apparent resistance of major Islamic banks to get involved in Islamic venture capital investment, ii) biasness against long-term investment; iii) underutilization of mushaarakah and mudaarabah mode of financing, iv) preference of expansion stage over seed capital by major venture capital institutions; v) lack of awareness on Islamic venture capital investment; vi) overreliance on government intervention. Practical Implications: This paper holds significant implications for the venture capital industry players because it provides gap which needs to fill to make the industry a success. Originality/Value of Paper: This paper sheds new light on the development of Islamic venture capital in Malaysia and constraints that stifle the progress of the industry. It also provides way forward for the industry.